Marriage as Discipleship: Luther's Praise of Married Life - Strohl, Jane E. (Dialog, 2008)
This article reviews the Luther's evangelical understanding of sexuality and marriage and its theological roots. Marriage is a demanding vocation. But while Luther speaks honestly about the perilous and painful challenges of marriage, he is also sensitive to the delights of love and courtship, giving beautiful expression to the joys of marriage.